Pipelines : emerging technologies and design criteria - Islam, Rafiqul, 1959- (Gulf Professional Publishing, 2023)
Pipelines: Emerging Technologies and Design Criteria, the latest release in the Sustainable Oil and Gas Development series, delivers the tools needed to understand more environmentally-friendly design, construction and maintenance of oil and gas pipelines. Designed to introduce ideal solutions and current state-of-the-art practices, the reference includes guidelines on environmental impact assessment and sustainable route design as well as the sustainability of additives and power systems. Material selection, real-time processing of smart well data and remote sensing are also discussed. Rounded out with inspection tools and emerging technology such as novel corrosion protection, this book gives pipeline engineers a guide on safer alternatives and upcoming guidelines in the race to reduce emissions.
Keywords: Petroleum pipelines.; Petroleum pipelines -- Design and construction.; Gas pipelines.; Gas pipelines -- Design and construction.; elektronické knihy; electronic books